Adult-Onset Gilles de la Tourette Syndrome: Psychogenic or Organic? The Challenge of Abnormal Neurophysiological Findings - Versace, Viviana; Campostrini, Stefania; Sebastianelli, Luca; Soda, Mirco; Saltuari, Leopold; Lun, Sigrid; Nardone, Raffaele; Kofler, Markus (Frontiers in Neurology, 2019)
Gilles de la Tourette syndrome (GTS) is characterized by multiple motor and vocal tics. Adult-onset cases are rare and may be due to “reactivation” of childhood tics, or secondary to psychiatric or genetic diseases, or due to central nervous system lesions of different etiologies. Late-onset psychogenic motor/vocal tics resembling GTS have been described. Neurophysiology may serve to differentiate organic from functional GTS. Altered blink reflex prepulse inhibition (BR-PPI), blink reflex excitability recovery (BR-ERC), and short-interval intracortical inhibition (SICI) have been described in GTS. We report a 48-years-old male, who developed numerous motor/vocal tics two months after sustaining non-commotional craniofacial trauma in a car accident. Both his father and brother had died earlier in car crashes. He presented with blepharospasm-like forced lid closure, forceful lip pursing, noisy suction movements, and deep moaning sounds, occurring in variable combinations, without warning symptoms or internal “urge”. Tics showed low distractibility and increased with attention. Standard magnetic resonance imaging, electroencephalography, and evoked potentials were unremarkable. Neuropsychology diagnosed moderately impaired intellect, attention, and executive functions. Psychiatric assessment revealed somatization disorder and generalized anxiety. BR-PPI was unremarkable, while BR-ERC was enhanced, even showing facilitation at short intervals. SICI was markedly reduced at 1 and 3 ms and intracortical facilitation (ICF) was enhanced at 10ms. The patient fulfilled Fahn and Williams’ diagnostic criteria for a psychogenic movement disorder. Neurophysiology, however, documented hyperexcitability of motor cortex and brainstem. We suggest that – similar to what has been reported in psychogenic dystonia – a pre-existing predisposition may have led to the functional hyperkinetic disorder in response to severe psychic stress.